KAJIAN EMPIRIS PENGARUH CORPORATE SOCIAL RESPONSIBILITI TERHADAP NILAI PERUSAHAAN DENGAN DIMODERASI OLEH GOOD CORPORATE GOVERNANCE PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (Research Institution and Community Service Wijaya Kusuma Surabaya University, 2014)
This study aimed to examine the effect of corporate social responsibility to corporate value are moderated by good corporate governance in companies listed on the Indonesia Stock Exchange. This study is adopted from previous studies about the influence of corporate social responsibility on corporate value with the percentage management ownership as a moderasi variable conducted by Nurlela and Islahuddin (2008) on companies listed on the Jakarta Stock Exchange. This study replicates previous research by adding the moderasi variable that is good corporate governance consisting of a board of directors, audit committee and board of directors. Sampling technique used purposive sampling with criteria: Companies other than the Banking and Financial Institutions sectors listed in the Indonesia Stock Exchange, publishes annual report and sustainability reporting or other social information and have complete data. Based on these criteria obtained a sample size of 70 companies. The results using interaction regression shows that corporate social responsibility significantly affect the value of the company. While the ownership variables management, board of directors, audit committee and board of directors as a proxy for good corporate governance does not succeed moderate the influence of corporate social responsibility to corporate value.